Regionalism in Elizabeth Gaskell´s North and South - Vavřinová, Linda (Univerzita Pardubice, 2020)
This bachelor thesis focuses on the origin and characteristics of regionalism and its representation in the novel North and South by Elizabeth Gaskell. It examines the genre itself, its characteristics and purpose in the first half of the nineteenth century alongside the historical development of both regions during the heyday of the first industrial revolution. Furthermore, it also mentions the position of women of all classes at the time with their lives' hardships and delights.
Regionalismus v díle Elizabeth Gaskell Sever a jih
Keywords: Gaskell, Elizabeth; regionalismus; industrializace; 19. století; Británie; Anglie; Sever; Jih; dělnická třída; střední třída; ženy; Gaskell, Elizabeth; regionalism; industrialization; 19th century; Britain; England; North; South; workingclass; middle class; women